Increasing Digital Literacy Through Video Based Learning in Balam Jaya Kampar Village - Zuryani, Hilmah; Kurniasih, Cut Endang; Rabialdy, Fakhri; Teguh, Teguh; Maulana, Adrian; Alfiah, Diyana (Universitas Negeri Medan, 2023)
Watching is one of the daily activities carried out by all levels of society, young and old to children. In the digital era, many children do not understand what they are watching and receive harmful information. The fact is that watching activities provide many benefits, such as getting information anywhere and anytime easily. The purpose of this activity is to provide education to students through digital literacy that there is a lot of learning that can be taken from watching activities and developing writing, understanding, and listening skills. The method used in this activity is Video Based Learning which is the delivery of learning through video by showing films. The results showed that the percentage level of video eligibility was 75% with good qualifications. Based on the results of the study, it can be concluded that the Video Based Learning method is feasible to use in the learning process